As organizações sociais e as ações governamentais em cultura: ação e política pública no caso do estado de São Paulo - Bittencourt, Lúcio Nagib (2014)
The present thesis addresses the operationalization of cultural public policies, focusing on the São Paulo State Government experience with the so-called Social Organizations arrangement. Literature reviews were developed regarding how the Brazilian federal government has acted on this issue so far, about Brazilian studies of cultural policies in a comparative perspective, as well as in relation to the referred specific arrangement now in place for 10 years in the State of São Paulo. Based on those reviews, it is hereby espoused that policies in question are complex and have at least three specificities, i.e., they are metapolicies, since not only their results, but also their processes, are perceived as a cultural project; they connect loose and minimal agreements regarding the role that governments should play in this field, resulting in vagueness about their goals; nonetheless, it is acknowledged the insufficient data available on the actual daily performance of this specific arrangement. In that sense, 31 semi-structured interviews were conducted in the State Department of Culture, with Social Organization managers and technicians, as well as personnel acting on the cultural arena although not directly involved in the arrangement. Great multiplicity was indeed identified: governmental and non-governmental organizations work together; different organizational structures, personal experiences, descriptions about process sequences, actions performed, questions asked, and expectations about the policy they were supposed to operate through this arrangement. Therefore, it is hereby suggested that the notion of public action in hybrid arenas is of utmost relevance for recognition and handling of the complexities involved in public policies operationalization, as in the case of the referred arrangement of Social Organizations regarding the topic of culture. Through this concept, the recognition and connection between different people, ideas and structures involved in its daily functioning becomes possible, as well as in relation to other languages of public actions involved - being the public policies one of them - and the uncertainties which compose the sociotechnical controversies experienced in the arena, becoming hybrid. In this context, dialogue amplification emerges as an alternative for the construction and learning of new routes regarding the practice of cultural governmental actions.